THE HUMAN LABOR RIGHT OF REFUGEES IN THE STATE OF MATO GROSSO DO SUL (Revista Paradigma, 2022)
In Brazil, from the nationally widespread culture that considers work as a dignifying instrument of a person, access to labor acquires unique relevance in the effective insertion of refugees in the community, being also, a mechanism of reestablishment of its dignity. Therefore, the present research proposes to analyze the mechanisms, both public and social order, to ensure the enjoyment of the human right to work by refugees in the State of Mato Grosso do Sul. Thus, the concept of refuge, as well as the provisions of the right to work in international documents and related national legislations, is analyzed at first, so the main public policies adopted by the Brazilian Government to guarantee the human labor right to refugees can be highlighted next. Finally, it investigates the mechanisms that help refugees' access to work in the State of Mato Grosso do Sul, from the perspective of different institutions. For this, the work uses the deductive method, with the types of exploratory, bibliographic and documentary research.Key Words: Refuge; Labor Right; Public Policies; Social Policies; Mato Grosso do Sul.